THE DIFFICULTIES OF STUDENTS IN TRANSLATING TEXT ENGLISHRECOUNT TEXT TO BAHASA INDONESIA ATSEMPOA SIP TITIKUNING - Rizki Amalda; Felizabeth Maria Manullang; Yolanda Novita Silaban (elt, 2022)
The purpose of this research is to examine the difficulties that student's face during the translation process, as well as the reasons why students have difficulty going to translate English recount text into Indonesian text. analyzing fifth, sixth and seventh grade students of Sempoa Sip Titikuning and SDN 064018 Years 2021 / 2022. The study employs a descriptive qualitative technique to describe the specifics of the students' difficulties and their process of trying to translate recount text into English to Indonesia. In order to know the result of the analysis carried out and to describe the difficulties encountered by the student’s, the researcher first reads the text, analyzes the text, writes and completes the students' translation assessment. Difficulty arranging words, loss of vocab, and comprehension of the text's translation.. Additionally, the highest proportion from the linguistic considerations is 70% of 20 students, while the highest percentage from the non-linguistic considerations 70% of 20 student’s. Which languagelinguistic considerations & non - linguistic considerations have the same result of high percentages. Keywords : The difficulties of student's, analysis of the student's process through Translate, Recount Text.